Two-dimensional magnesium oxide nanosheets reinforced epoxy nanocomposites for enhanced fracture toughness. (26th January 2018) - Balguri, Praveen Kumar; Samuel, D G Harris; Guruvishnu, T; Aditya, D B; Mahadevan, S M; Thumu, Udayabhaskararao
Abstract: Metal oxide nanoparticles have been used as excellent reinforcements to enhance mechanical properties of polymers, natural composites, and ceramics. To date, a major portion of metal oxides used as nanofillers is three dimensional spherical nanoparticles. In the last decade, two-dimensional (2D) materials such as graphene have been widely investigated to improve the mechanical and electrical properties of polymer materials. In this paper, 2D Magnesium oxide (MgO) nanosheets reinforced epoxy composites (0.1, 0.2 and 0.4 wt%) are fabricated and studied for their ability to resist the propagation of preexisting flaw by conducting fracture toughness test for K IC, critical stress intensity factor. This property is an important mechanical property for designing applications in various engineering technologies. Our results show that the MgO with 0.2 wt% is the optimized level to improve the fracture toughness of the epoxy polymer by 47%.